2020
DOI: 10.1109/tpel.2019.2959736
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Microchannel Cooling of Multiple Power Devices With Compact Flow Distribution for High Power-Density Converters

Abstract: In this work, we describe a new approach for compact and energy-efficient cooling of converters where multiple miniaturized microfluidic cold-plates are attached to transistors providing local heat extraction. The high pressure drop associated with microchannels was minimized by connecting these cold-plates in parallel using a compact 3D-printed flow distribution manifold. We present the modeling, design, fabrication and experimental evaluation of this microfluidic cooling system and provide a design strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Now the matrix that incorporates all independent switching states, SI(N), can be derived by concatenating matrices SPS(N) and SSW(N), leading to a (N-2) x (N-1) matrix. An example of the SI( 7) is presented in (8).…”
Section: The Extended Zss Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Now the matrix that incorporates all independent switching states, SI(N), can be derived by concatenating matrices SPS(N) and SSW(N), leading to a (N-2) x (N-1) matrix. An example of the SI( 7) is presented in (8).…”
Section: The Extended Zss Matrixmentioning
confidence: 99%
“…The high switching frequency capabilities of these devices (in the hundreds of kHz to a few MHz range) allow the minimization, even elimination, of the magnetic components and the replacement of electrolytic capacitors with lightweight and reliable ceramic capacitors [7]. Moreover, the overall efficiency and power density gain brings a further reduction to the physical dimensions of the cooling system [8].…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that the device worked normally in the range of 2-6 GHz when it experienced a heat dissipation density of 400 W/cm 2 . In 2020, researchers at EPFL proposed an approach of codesigning an electronic device with integrated microchannels on a GaN-on-Si substrate [27][28][29] . A full wave bridge AC-DC convertor based on Schottky diodes on a GaN layer with a cooling manifold microchannel embedded inside the Si substrate is demonstrated, showing a temperature increase of approximately 60 K when it experiences a heat flux of 1.7 kW/cm 2 and an average heat flux of 417 W/cm 2 at the device level upon working.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional air cooling method has been unable to meet the requirements of high power density heat dissipation [7]. Liquid cooling has become an attractive solution for the cooling of power electronics converters due to its high cooling capacity.…”
Section: Introductionmentioning
confidence: 99%